Deformed Ω for realisation of LH characteristics. (22nd January 2013) - Mishra, Debasis; Poddar, D.R.; Mishra, R.K.
Two new types of unit cell structures are proposed to be used in an array for realisation of double negative metamaterial characteristics. The S parameters of the proposed structures are extracted for comparisons with HFSS full–wave simulation. Such new deformed omega structures are capable of exhibiting enhanced negative refractive index bandwidth with proper choice of the dimensions and periodicity. Similarly, suitably changing dimensions and periodicity narrow–band negative refractive index can be realised.